2018
DOI: 10.26748/ksoe.2018.32.6.447
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Application of Two-Dimensional Numerical Tank using Desingularized Indirect Boundary Integral Equation Method

Abstract: In this study, a two-dimensional fully nonlinear transient wave numerical tank was developed using a desingularized indirect boundary integral equation method. The desingularized indirect boundary integral equation method is simpler and faster than the conventional boundary element method because special treatment is not required to compute the boundary integral. Numerical simulations were carried out in the time domain using the fourth order Runge-Kutta method. A mixed Eulerian-Lagrangian approach was adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Zhou et al [15] compared their results of various motion modes with those reported by Bai and Eatock Taylor [14]. Recently, Oh et al [16] solved the radiation problem for a wave maker by applying the desingularized indirect PNWT. Feng et al [17] solved the linear diffraction and radiation problems for a hemispheric buoy by calculating the integral of the Rankine source on the free surface panel.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [15] compared their results of various motion modes with those reported by Bai and Eatock Taylor [14]. Recently, Oh et al [16] solved the radiation problem for a wave maker by applying the desingularized indirect PNWT. Feng et al [17] solved the linear diffraction and radiation problems for a hemispheric buoy by calculating the integral of the Rankine source on the free surface panel.…”
Section: Introductionmentioning
confidence: 99%
“…In the three-dimensional NWT, the physical wave tank experiments are numerically simulated through techniques such as the boundary element or finite element methods, which is an analysis technique for nonlinear wave analysis and nonlinear motion analysis. Koo and Kim (2004), Oh et al (2018), and Wu and Eatock Taylor (1995) have conducted analyses using a two-dimensional nonlinear NWT. In particular, Wu and Eatock Taylor (1995) analyzed the radiation problem with a circular cylinder using the boundary element method and finite element method for a two-dimensional nonlinear NWT.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the MEL method, which is flexible for the analysis of the strong nonlinearity of free surface and wave-body interactions, was applied using various solution methods of the Laplace equation such as boundary element method (BEM), finite element method (FEM), and harmonic polynomial cell (HPC) (Longuet-Higgins and Cokelet, 1976;Wu et al, 1998;Shao and Faltinsen, 2014). Because the mentioned solution method of the Laplace equation inevitably requires matrix operation, the MEL method, which reconstructs the free surface grid every time step to reflect the completely nonlinear free surface, requires high computational costs for calculations of a solution of boundary value problem (Oh et al, 2018). In contrast, the higher-order spectral (HOS) method of Dommermuth and Yue (1987), based on a higher-order analysis method, can determine the solution of the boundary value problem using the fast Fourier transform (FFT) without a matrix operation.…”
Section: Introductionmentioning
confidence: 99%